Growth Promotion of Salicornia bigelovii by Micromonospora chalcea UAE1, an Endophytic 1-Aminocyclopropane-1-Carboxylic Acid Deaminase-Producing Actinobacterial Isolate - El-Tarabily, Khaled A.; AlKhajeh, Abdulmajeed S.; Ayyash, Mutamed M.; Alnuaimi, Latifa H.; Sham, Arjun; ElBaghdady, Khaled Z.; Tariq, Saeed; AbuQamar, Synan F. (Frontiers in Microbiology, 2019)
Salicornia bigelovii is a promising halophytic crop for saline soils in semi-arid regions. This study was designed to characterize isolates of endophytic actinobacteria from S. bigelovii roots and evaluate the effects associated with plant growth promotion. Twenty-eight endophytic isolates obtained from surface-sterilized roots of S. bigelovii were initially selected based on their production of 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase in vitro in a chemically defined medium. Application of Micromonospora chalcea UAE1, possessing the highest ACC deaminase activity, to S. bigelovii seedlings significantly enhanced the plant growth under gnotobiotic and greenhouse conditions. This was clear from the increases in the dry weight and length of both shoot and root, and seed yield compared to the non-ACC deaminase-producing isolate Streptomyces violaceorectus, or control treatment. The growth promotion was also supported by significant increases in the content of photosynthetic pigments and the levels of auxins, but significant decreases in the levels of ACC in planta. Under greenhouse conditions, M. chalcea recovered from inside the inoculated roots in all samplings (up to 12 weeks post inoculation), suggesting that the roots of healthy S. bigelovii are a suitable habitat for the endophytic actinobacterial isolates. Pure cultures of M. chalcea were not capable of producing auxins, gibberellic acid, cytokinins or polyamines in vitro. This indicates that the growth promotion is most likely to be due to the reduction of the endogenous levels of the stress hormone ethylene. Our findings suggest that growth and yields of S. bigelovii can be enhanced by the field application of the endophyte M. chalcea UAE1. This study is the first to report potential endophytic non-streptomycete actinobacteria to promote the growth of halophytic plants in semi-arid zones under greenhouse conditions.